Sy123
This too shall pass
- Joined
- Nov 6, 2011
- Messages
- 3,725
- Gender
- Male
- HSC
- 2013
Re: HSC 2013 2U Marathon
converges to zero
One way is that:
![](https://latex.codecogs.com/png.latex?\bg_white \lim_{n \to \infty} (n-1)x^{n+1} = \lim_{n \to \infty} nx^{n+1} - \lim_{n \to \infty} x^{n+1} )
We know the second limit converges to zero, because
(sketch the graph of 2^(-n))
![](https://latex.codecogs.com/png.latex?\bg_white =\lim_{n \to \infty} nx^{n+1} = x \times \lim_{n \to \infty} nx^n = x \times 0 = 0 )
Yep well done, however for the last part I would have liked some better justification of how the term,View attachment 28510 I hope it's correct... may not be thoughlol
One way is that:
We know the second limit converges to zero, because